DAMPAK METODE PEMBELAJARAN BERBASIS GAME-BASED LEARNING TERHADAP PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR : SYSTEMATIC LITERATURE REVIEW - Aditya Agung Saputra; Haryadi; Bernadus Wahyudi Joko Santoso (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the impact of implementing game-based learning methods on learning. Five articles were analyzed to identify the impact of implementing game-based learning methods on science learning in elementary schools. The analysis results show that the implementation of game-based learning methods has a positive impact on science learning. Game-based learning methods have various game designs that attract students' interest, allowing them to learn while playing. Overall, game-based learning has been proven to have a positive impact on science learning in elementary schools.